Clinical and pathogenetic justification for the use of therapeutic plasma exchange in the complex of preoperative preparation of patients with non-small cell lung cancer complicated by the inflammatory process - N. D. Ushakova; D. A. Rozenko; S. N. Tikhonova; D. A. Kharagezov; N. N. Popova (Южно-Российский онкологический журнал, 2024)
Purpose of the study. Determination of pathogenetic substantiation and indication criteria for the inclusion of extracorporeal detoxification methods in preoperative preparation of patients with non-small cell lung cancer (NSCLC) complicated by inflammation.Patients and methods. This study included the data on 222 patients with newly diagnosed stage I–IV NSCLC referred for elective surgical treatment to the Department of Thoracic Oncology, National Medical Centre for Oncology, in 2017–2019. Endogenous intoxication was evaluated in all patients depending on the leukogram results: leukocytic intoxication index (LII), body resistance index (BRI), reactive neutrophil response (RNR), and neutrophil-lymphocyte ratio (NLR). Indicators of the inflammatory response, i. e. interleukin 6 and procalcitonin, were also studied.Results. 36.5 % of NSCLC patients developed inflammation. That over 70 % of the NSCLC patients showed pronounced clinical and laboratory signs of endogenous intoxication and inhibited protective systems of homeostasis. Initial sub- or decompensated endotoxicosis together with reduced overall reactivity of the body poses a high risk of systemic inflammatory response to antitumor surgical treatment. This justifies the inclusion of extracorporeal detoxification into preoperative preparation of this category of patients as an active preoperative therapy.Conclusions. Simultaneous elevation of LII, RNR and NLR characterizing the presence of endotoxicosis in sub- and decompensation of endogenous intoxication by own physiological detoxification systems requires an active preoperative preparation with extracorporeal detoxification.